The problem of aggressiveness, self-regulation and adaptation of the personality - E V Tarasova (Peoples' Friendship University of Russia (RUDN University), 2010)
The article analyzes the manifestations of aggressiveness in the children-parents relationships. Revealed features of effective strategies for correction of aggression, based on self-control and self-regulation of personality.